Analysis of The Performance Policy of The Bukittinggi City Government Towards Micro, Small and Medium Enterprises And Empowerment of Street Vendors in Islamic Economic Perspective - Sari, Oktri Lola; Izmuddin, Iiz (Department of Public Administration, 2023)
The main problem that is being studied by the authors in the research for this thesis is that street vendors (PKL) are informal sector entrepreneurs. There are those who sell at certain locations, there are also those who are mobile from one place to another (using a pickaxe, stroller or the like) lining up groceries, drinks and other consumer goods at retail. Street vendors generally have small capital, not infrequently if sometimes they are just a tool for capital owners to get modest commissions/rewards. This research is a qualitative approach using the Nvivo application using primary data and secondary data. The analytical method used is a descriptive approach, namely identifying various problems faced by street vendors and SMEs by using analysis using the Nvivo application. The results of the study found that the results of research that had been carried out on PKL Micro Business Actors in Bukittinggi City, that the Bukittinggi City MSME and Trade Cooperative Service was guided by IKU (Main Performance Indicators). determined by the Regional Government and IKU of the Bukittinggi City Cooperative, UKM and Trade Office.